α-Galactosidase levels in irritable bowel syndrome subtypes and quality of life of patients (Annals of Medical Research, 2021)
Aim: There is a requirement for a reliable serologic marker that can be used for the diagnosis of Irritable Bowel Syndrome (IBS). The aim of our study was to research whether serum levels of Alpha-galactosidase (AG) is associated with IBS and to assess quality of life (QOL) of IBS patients.Materials and Methods: 110 adult patients who were diagnosed with IBS were evaluated. 90 patients and 25 healthy volunteers wereincluded. Patients were classified into subtypes: IBS-Diarrhea (IBS-D), IBS-Constipation (IBS-C), IBS-Mixed (IBS-M), and 30 patients wereenrolled for each group. We administered the Short Form 36 (SF-36) to participants to evaluate QOL. Serum AG levels of participants was determined.Results: The mean AG levels of IBS-C and control group were significantly lower than the other groups (p